The Effect of Metformin and Cinnamon on Serum Anti-Mullerian Hormone in Women Having PCOS: A Double-Blind, Randomized, Controlled Trial - Wiweko, Budi (J Hum Reprod Sci, 2017)
BACKGROUND: Polycystic ovary syndrome (PCOS) is known to be associated with insulin resistance and anti-Mullerian hormone (AMH), leading to the use of insulin-sensitizing agents (ISAs) to manage PCOS. Metformin is the most widely used ISA to treat irregular menstruation; however, the gastrointestinal side effects are quite debilitating. The development of herbal medicines such as bioactive fraction DLBS3233 offers a possibly effective treatment with minimal side effects. AIM: To determine the effect of metformin and DLBS3233 on serum AMH level. MATERIALS AND METHODS: This study was a double-blind, randomized, controlled trial conducted between March 2013 and June 2015 at Yasmin Clinic, RSCM Kencana, Jakarta and Hasan Sadikin Hospital, Bandung. The patients with PCOS were diagnosed using the Rotterdam criteria. All participants received daily treatment consisting of 1500 mg metformin divided into two doses or 100 mg DLBS3233 for 6 months. An evaluation of serum AMH level was conducted before and after the completion of therapy. RESULTS: Twenty patients received metformin, whereas 18 patients received DLBS3233. The levels of AMH prior to the intervention were 9.30 ± 5.06 ng/mL and 11.27 ± 6.47 ng/mL. After 6 months of therapy, we found that the decrease in AMH level was higher in the metformin group compared to the DLBS3233 group (ΔAMH = 1.83 ng/mL, P = 0.003 and ΔAMH = 1.15 ng/mL, P = 0.077, respectively). However, more side effects were observed in the metformin group compared to the DLBS3233 group (P = 0.01). A total of seven patients (18.42%) were confirmed as pregnant during the study. CONCLUSION: There was a significant decrease in the serum AMH level after administration of either metformin or DLBS3233.